2008
DOI: 10.1097/ogx.0b013e318173538e
|View full text |Cite
|
Sign up to set email alerts
|

Transmural Migration of Retained Surgical Sponges

Abstract: Retained surgical sponges have been reported to occur after a diversity of surgical procedures, but transmural migration is a very unusual sequela. This article reports a case in which a retained surgical sponge eroded from the intra-abdominal space into the intestinal lumen, migrated distally, and spontaneously passed with defecation 12 weeks after the cesarean section. We performed a systematic review of the literature in Pubmed and found 64 cases of transmural migration of retained surgical sponges. Sixty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 45 publications
0
89
1
3
Order By: Relevance
“…A review of 64 cases of transmural migration of retained surgical sponges, mainly after intra-abdominal surgery, showed that 75% of the cases involved intestinal migration, whereas only 7 cases described migration into the bladder [6]. Spontaneous transurethral protrusion is rare, and the present authors have the knowledge of the report of only one case [8].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…A review of 64 cases of transmural migration of retained surgical sponges, mainly after intra-abdominal surgery, showed that 75% of the cases involved intestinal migration, whereas only 7 cases described migration into the bladder [6]. Spontaneous transurethral protrusion is rare, and the present authors have the knowledge of the report of only one case [8].…”
Section: Discussionmentioning
confidence: 69%
“…Retained surgical sponges have been reported to occur after a diversity of surgical procedures such as abdominal, thoracic, cardiovascular, orthopaedic, and even neurosurgical operations [2,6]. Following retention, they have revealed themselves as intra-abdominal masses, in intestinal fistulae, by intestinal obstruction after transmural migration into the intestinal lumen, by protrusion into the gastric antrum from the first part of the duodenum, and into the rectum.3 Most cases present as a mass or with subacute intestinal obstruction, although rarely do they result in fistulas, free perforation or even extrusion [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration of textiloma in the intestinal lumen is considered a rare complication and occurs as a result of inflammation of the intestinal wall leading to necrosis [1]. Few cases have been reported in the literature: a case involving intestinal lumen migration recorded in Japan [8] with Zantvoord et al [1] noting 65 cases in total including one of theirs.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it often leads to additional and repeated surgery hence associated with higher rates of morbidity and mortality. On the other hand, there are very few cases relating to spontaneous rectal expulsion of textiloma or other retained surgical foreign bodies [1]. Thus we hereby report a case of textiloma expelled in faeces in a 26-year-old female with previous medical history of Csection for dynamic dystocia a year prior to her admission.…”
Section: Introductionmentioning
confidence: 91%